Reshaping the urban street: a case study(Saadoun Al-Suwaihli Street) Misrata (Journal of Academic Research, 2024)
This research paper focused on urban design principles, particularly concerning Saadoun Al-Suwaihli Street in Misrata. It highlights the significance of streets as public spaces for social interactions and community vitality. The research emphasizes the need to balance pedestrian needs with vehicular traffic, addressing issues like congestion, parking shortages, and neglected public areas. Through various data collection methods, including field visits and surveys, the study identifies key challenges and proposes solutions for urban revitalization. Suggestions include reopening blocked intersections, creating parking facilities, revitalizing public spaces, and enhancing pedestrian amenities. The vision for the street aligns with creating a 'woonerf' environment, prioritizing pedestrian safety and community engagement. The study draws on a conceptual framework to understand the relationship between urban design quality and user perception. Through site analysis and conceptualization, the research provides a comprehensive overview of the street's current state and potential improvements. Overall, the study underscores the importance of creating inclusive, pedestrian-friendly environments to enhance urban livability and foster community well-being.